An Electrochemical Sensing Platform Based on Graphene Oxide and Molecularly Imprinted Polymer Modified Electrode for Selective Detection of Amoxicillin - YANIK, SERHAT (WILEY-V C H VERLAG GMBH, 2021)
An electrochemical sensing platform based on composite material, consisting of molecularly imprinted polymer coated on graphene oxide (MIP-GO), was developed for selective and sensitive analysis of amoxicillin (AMOX). TheMIP-GOcomposite, which was fabricated by sol-gel polymerization after removal of template molecule, was deposited as a thin film on glassy carbon electrode, and then was electrochemically characterized by cyclic voltammetry and differential pulse voltammetry. The linear response for the determination ofAMOXwas obtained in the concentration range from 5.0x10(-10)to 9.1x10(-7) M under the most proper conditions and the detection limit was found to be 2.94x10(-10) M.
Keywords: Imprinted sol-gel; graphene oxide; electrochemical sensor; amoxicillin; WALLED CARBON NANOTUBES; SOL-GEL; SENSITIVE DETERMINATION; O-PHENYLENEDIAMINE; QUANTUM DOTS; SENSOR; FILM; NANOCOMPOSITE; RECOGNITION; SAMPLES